The Effect of Ethical Orientation and Professional Commitment on Earnings Management Behavior - Greenfield, A. C. (Journal of business ethics, 2008)
The purpose of this study is twofold. The first objective is to examine the impact of an individual’s ethical ideology and level of professional commitment on the earnings management decision. The second objective is to observe whether the presence of a personal benefit affects an individual’s ethical orientation or professional commitment within the context of an opportunity to manage earnings. Using a sample of 375 undergraduate business majors, our results suggest a significant relationship between an individual’s ethical orientation and decision-making. Further, participants with higher levels of professional commitment seem to be less likely to engage in earnings management behavior and less likely to behave opportunistically. These results have the potential to add to our understanding of certain behaviors in entry-level personnel and should be of interest to managers, practitioners, academicians, and researchers.